Evaluating an intervention to promote access to mental healthcare for low language proficient migrants and refugees across Europe (MentalHealth4All): study protocol for a pretest–post-test cross-national survey study - Fang Wang; Mike Mösko; Demi Krystallidou; Yuhui Chen; Liza G G van Lent; Saskia Hanft-Robert; Ilaria Galasso; Barbara Schouten; Antoon Cox; Sona Hodakova; Chiara Rao; Koen Kerremans; et al. (BMJ Open)
Background Migrants and refugees with low language proficiency (LLP) in the dominant language of their host country have a higher risk of suffering from certain mental health disorders compared with non-migrant populations. They are also more likely to experience a lack of access to mental healthcare due to language-related and culture-related barriers. As part of the MentalHealth4All project, a digital multilingual communication and information platform was developed to promote access to mental healthcare for LLP migrants and refugees across Europe. This paper describes the study protocol for evaluating the platform in practice, among both health and/or social care providers (HSCPs) and LLP migrants and refugees.Methods and analysis We will conduct a pretest–post-test cross-national survey study to evaluate the platform’s effect evaluation (primary objective) and process evaluation (secondary objective). The primary outcomes (measured at T0, T2 and T3) are four dimensions of access to mental healthcare services: availability, approachability, acceptability and appropriateness of mental healthcare. Secondary outcomes (measured at T2) are: actual usage of the platform (ie, tracking data), perceived ease of use, usefulness of content, comprehensibility of information, attractiveness of content and emotional support. Participants will be recruited from nine European countries: Belgium, Germany, Italy, Lithuania, the Netherlands, Poland, Slovakia, Spain and the UK. Using convenience sampling through professional networks/organisations and key figures, we aim to include at least 52 HSCPs (ie, 6–10 per country) and 260 LLP migrants (ie, 30–35 per country). After completing a pretest questionnaire (T0), participants will be requested to use the platform, and HSCPs will participate in an additional personalised training (T1). Next, participants will fill out a post-test questionnaire (T2) and will be requested to participate in a second post-test questionnaire (T3, about 6–8 weeks after T2) to answer additional questions on their experiences through a brief phone interview (T3 is optional for migrants/refugees).Ethics and dissemination For all nine countries, the ethical review board of the participating university (hospital) has assessed and approved the protocol. If successful, the MentalHealth4All platform will be made publicly available to help improve access to mental healthcare services, as well as HSCPs’ cultural competencies in delivering such services, for any LLP migrants and refugees across Europe (and beyond). Findings will also be disseminated through peer-reviewed journals and conferences.Registration details The ‘MHealth4All project’ was prospectively registered on Open Science Framework, DOI: 10.17605/OSF.IO/U4XSM.